A Study of the Determinants Influencing Customer Satisfaction in the Medical Tourism Industry in Jordan - Alsarayreh, Mohammad Nayef; Mahasneh, Mohammad Sultan Majed; Al Nawaiseh, Kafa Hmoud Abdallah (International Review of Management and Marketing, 2017)
The aim of the research is to test what determines customer satisfaction of the people seeking treatment in Jordan. For the purposes of this research, the researcher used the descriptive analytical method to identify and analyze the factors that affect customer satisfaction about medical tourism and health services provided to tourists and people accompanying him in Jordan. The study belongs to analytical explorative studies that follow the approach of collecting and analyzing data to reach the results where a questionnaire was distributed to a number of employees of five star hotels in the city of Aqaba. A total of 120 copies of the questionnaire were distributed, of which 95 were returned, and (20) copies were excluded. So the was based on (75) copies of the questionnaire distributed to a number of patients coming to Jordan for the purpose of medical tourism whose data were obtained by the researcher. The research was based on Expectations Confirmation Theory (ECT), Kanomodel, and customer satisfaction. The questionnaire developed by Pham (2015) was used after it has been modified to suit environmental conditions in Jordan. The main variables included independent variables: financial considerations, quality of services, and medical facilities; a dependent variable which is customer satisfaction, and an intermediate variable which is the Jordanian environment (including culture, location and government). Four hypotheses were developed to clarify the relationship between (1) financial considerations and customer satisfaction, (2) quality of service and customer satisfaction, (3) medical facilities and customer satisfaction, and (4) the Jordanian environment and customer satisfaction. To answer the research questions comprehensively, the study adopted quantitative research design. The sample consisted of (75) patients coming to Jordanfor the purpose of medical tourism. The questionnaire was formed of 46 questions. Multiple and hierarchical regression was applied to the four basic hypotheses. The regression lines produced a model known as customer satisfaction based on three independent and intermediate variables. The study concluded that the cost factor is closely related to customer satisfaction. Foreign exchange rates positively affect customer satisfaction. Professionalism has a positive impact on customer satisfaction. Rapid service has a positive impact on customer satisfaction. Keywords: medical tourism, customer satisfaction, customer expectation. JEL Classifications: Z32, L83; M31